Intensification of Foam Layered Apparatus by Foam Stabilization - Liaposhchenko, O.; Khukhryanskiy, O.; Moiseev, V.; Ochowiak, M.; Manoilo, E. (Sumy State University, 2018)
In this work the expanded models are studied for foaming apparatuses with gratings made of tubes for different diameters. The problem of intensification of foam devices using coarse-grating lattices is considered. The possibility of deep cleaning and practically complete cleaning of gases from ammonia and fluoride compounds with their separate absorption is noted. The series of experimental dependencies for the main parameters of the process are given. The possibility of effective mass-exchange processes in an intensive foam layer on counter-current coarsegrating lattices is confirmed. The controversial requirements for equipment have been given despite the large number of existing machines for mass transfer processes, as well as the development of new high-intensity and efficient equipment for environmental technologies in many industries is considered.
Keywords: industrial gas emissions; hydrodynamics; mass transfer; foam apparatus; foam layer; purification process; stabilization of foam layer; intensification of the process